The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13014-022-02186-0
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models predict overall survival and progression free survival of non-surgical esophageal cancer patients with chemoradiotherapy based on CT image radiomics signatures

Abstract: Purpose To construct machine learning models for predicting progression free survival (PFS) and overall survival (OS) with esophageal squamous cell carcinoma (ESCC) patients. Methods 204 ESCC patients were randomly divided into training cohort (n = 143) and test cohort (n = 61) according to the ratio of 7:3. Two radiomics models were constructed by radiomics features, which were selected by LASSO Cox model to predict PFS and OS, respectively. Clini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This study developed splenic CT image‐based survival prediction models for patients with ESCC who had undergone dRT. Several previous studies have demonstrated the utility of radiomics in predicting the survival prognosis of patients with EC 9–12,24–26 . Delta‐radiomics encompasses a vast amount of time‐dependent information, allowing the dynamic assessment of complete image changes throughout the treatment period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study developed splenic CT image‐based survival prediction models for patients with ESCC who had undergone dRT. Several previous studies have demonstrated the utility of radiomics in predicting the survival prognosis of patients with EC 9–12,24–26 . Delta‐radiomics encompasses a vast amount of time‐dependent information, allowing the dynamic assessment of complete image changes throughout the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics modeling based on magnetic resonance images of primary esophageal lesions to predict DFS and OS was established by Chu et al 24 The C‐index values of the training and validation groups were 0.714 and 0.729, respectively, and the OS prediction model scores for the respective groups were 0.730 and 0.712. Cui et al 25 predicted the PFS and OS of patients undergoing radiotherapy based on esophageal CT images, and the C‐index values were 0.81 and 0.79 for the PFS model and 0.72 and 0.71 for the OS model. Nevertheless, all these studies established their models based on images of the primary esophageal lesion, which more often reflect the biological characteristics of the primary tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies investigating machine learning methods for exploring prognostic risk factors in esophageal cancer, certain investigations focused on extracting mRNA transcriptomic data from public databases like The Cancer Genome Atlas (TCGA) to assess the predictive capability of models for ORR or PFS 21 . Other studies aimed to identify novel biomarkers that could serve as predictors of treatment outcomes 22 . However, these studies were limited to patients undergoing CCRT for esophageal cancer and did not encompass patients receiving different treatment regimens or speci cally focus on elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…The latest fashion in AI application is represented by the role of radiomics in the prediction of response to surgical or medical treatment in cancer patients [ 47 , 48 , 49 , 50 , 51 ]. In this way, radiomics can be used to speculate as to the risk category classification of patients and to predict patient overall survival and risk of complication [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%